2013
DOI: 10.1002/phy2.83
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting Amadori-modified albumin formation improves biomarkers of podocyte damage in diabetic rats

Abstract: Recent studies have shown that urinary excretion of podocyte proteins is an indicator of podocyte injury, and that podocyte abnormalities and elevated concentrations of Amadori-modified glycated albumin (AGA) are linked to the development of diabetic nephropathy and to each other. We evaluated relationships between urinary markers of podocyte damage, increased AGA and filtration function in rats made diabetic by streptozotocin injection and treated for 8 weeks with a compound that inhibits the formation of AGA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…An increase in serum GA concentration is followed by nephrin level increase in diabetic murine. Conversely, if serum GA level is reduced by controlling hyperglycemia, the urinary nephrin also decreased [32].…”
Section: Correlation Between Serum Glycated Albumin With Urinary Nephmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in serum GA concentration is followed by nephrin level increase in diabetic murine. Conversely, if serum GA level is reduced by controlling hyperglycemia, the urinary nephrin also decreased [32].…”
Section: Correlation Between Serum Glycated Albumin With Urinary Nephmentioning
confidence: 99%
“…A study by Cohen et al (2013) measured the level of glycated albumin, creatinine, albumin, and nephrin in diabetic murine compared to nondiabetic marines. This study demonstrated a positive linear correlation between GA and urinary nephrin (p<0,05 and r=0,58).…”
Section: Correlation Between Serum Glycated Albumin With Urinary Nephmentioning
confidence: 99%